Analisis Penggunaan Media Pembelajaran Smart Geo Terhadap Kemampuan Komunikasi Matematis Siswa Melalui Pendekatan CRT - Hidayatun Naimah, Nur; Ardi Saputro, Bagus; Tri Yulita, Kristina; Nuroso, Harto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to analyze the use of Smart Geo learning media on the mathematical communication skills of second-grade students at SDN Tandang 02 Semarang through the Culturally Responsive Teaching (CRT) approach. The research method employed is descriptive qualitative, with a total of 27 students as subjects. Data were collected through observations, interviews, documentation, and cognitive tests measuring students' mathematical communication skills in flat geometry integrated with Indonesian culture traditional houses. The results indicate that 48.1% of students have high mathematical communication skills, 33.3% are at a medium level, and 18.5% are low. The use of concrete media, Smart Geo, proved effective in facilitating understanding of the material, in line with students' cognitive development characteristics according to Piaget's theory. The CRT approach successfully made learning more relevant by connecting the material to local culture. These findings suggest that integrating concrete media and culturally based approaches can significantly enhance students' mathematical communication skills.